2023
DOI: 10.1111/hiv.13487
|View full text |Cite
|
Sign up to set email alerts
|

Advanced HIV disease: A review of diagnostic and prophylactic strategies

Abstract: Background Despite expanded access to antiretroviral therapy (ART) and the rollout of the World Health Organization's (WHO) ‘test‐and‐treat’ strategy, the proportion of people with HIV (PWH) presenting with advanced HIV disease (AHD) remains unchanged at approximately 30%. Fifty percent of persons with AHD report prior engagement to care. ART failure and insufficient retention in HIV care are major causes of AHD. People living with AHD are at high risk for opportunistic infections and death. In 2017, the WHO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…This analysis explored the prevalence of AHD at ART initiation and related mortality among PLHIV in Kinshasa, DRC, and associated age inequalities. Our findings reveal that AHD at treatment initiation among PLHIV was high, at 32%, which is consistent with global estimates 10 , 11 and a similar study in South Africa. 12 In partial support of our first hypothesis, AHD was more common among adolescents, males, and those who began treatment before 2015.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This analysis explored the prevalence of AHD at ART initiation and related mortality among PLHIV in Kinshasa, DRC, and associated age inequalities. Our findings reveal that AHD at treatment initiation among PLHIV was high, at 32%, which is consistent with global estimates 10 , 11 and a similar study in South Africa. 12 In partial support of our first hypothesis, AHD was more common among adolescents, males, and those who began treatment before 2015.…”
Section: Discussionsupporting
confidence: 92%
“…8,9 However, this positive news may mask an enduring burden of advanced HIV disease (AHD), defined as having CD4 cell count < 200 cells/μL or WHO clinical stages III and IV. 10 Approximately 30% of PLHIV globally have AHD 10,11 ; these patients are at increased risks for mortality (even after treatment initiation), opportunistic infections, and higher treatment costs than PLHIV without AHD. [10][11][12] Late linkage to care, delayed ART initiation, ART failure, and poor in-care retention are the main driving factors of AHD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last updated World Health Organization (WHO) report indicated that globally about 39.0 million people acquired HIV-1 and 630,000 people died from HIV-1-dependent problems at the end of 2022 [5]. Furthermore, HIV-1/AIDS provokes opportunistic infections including tuberculosis, cryptococcal infection, histoplasmosis, and severe bacterial infections; hepatitis B, and C co-infections [6][7][8]; and comorbidities such as cardiovascular, kidney, and liver disorders and cancer [9]. In the near future, COVID-19 and monkeypox virus infections could be possible challenges for clinicians and people with HIV-1 [10,11].…”
Section: Introductionmentioning
confidence: 99%